USE OF BOTULINUM TOXIN TYPE A IN THE TREATMENT OF MIGRAINE - Hayak Pereira Lopes, Maykon (Health and Society, 2025)
Patients with migraine often experience impacts on their personal, social, and professional lives. The disease not only impacts the individual’s quality of life but also results in costs for the healthcare system and society. Despite the impact on quality of life and the costs generated for society, the disease remains underestimated, with old, nonspecific treatments of moderate efficacy and frequent adverse effects, which limits patient adherence (NACAZUME, 2019). Recently, the administration of botulinum toxin type A (BTA) has been studied as an alternative to reduce long-term adverse effects observed with other prophylactic agents (PIOVESAN et al, 2017). Therefore, the objective of this study is to analyze the efficacy of migraine treatment with BTA. To this end, a systematic review of the literature on the use of BTA in migraine prophylaxis was conducted. Patients treated with botulinum toxin type A were observed to have significantly fewer migraine attacks per month, reduced severity, fewer days using acute medications, and a reduced incidence of migraine-associated vomiting.